Multitarget Therapy: An Effective and Safe Therapeutic Regimen for Lupus Nephritis - Zhou, Tianbiao; Zhang, Xialan; Lin, wenshan; Lin, Shujun (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Introduction: We evaluated the effectiveness and safety of various multitarget therapies for inducing remission in lupus nephritis patients. Methods: Randomized controlled trials (RCT) were identified and extracted from the Embase, PubMed, Chinese Biomedical Literature Database (CBM), and the Cochrane Library until Oct 31, 2018, investigations meeting inclusion criteria were extracted, and data were analyzed by meta-analysis. The total remission (TR; complete to partial remission), complete remission (CR), albumin, proteinuria levels, negative rate of anti-double-stranded DNA antibody (ds-DNA), negative rate of anti-nuclear antibody (ANA), and systemic lupus erythematosus disease activity index (SLE-DAI) were calculated using the software of RevMan 5.3. Results: Eleven RCTs were included and analyzed. The multitarget therapy group exhibited a higher value of CR (OR=3.06, 95%CI: 2.35-3.99, P﹤0.00001) as well as TR (OR=3.83, 95%CI: 2.77-5.31, P﹤0.00001) than those in the cyclophosphamide (CYC) group. In addition, multitarget therapies had more albumin (WMD=3.50, 95%CI: 1.04-5.95, P=0.005), greater albumin increases (OR=1.96, 95%CI: 0.63-3.29, P=0.004) and higher negative rates of ds-DNA (OR=2.13, 95%CI: 1.51-3.01, P﹤0.0001) and ANA (OR=2.82, 95%CI: 1.77-4.50, P﹤0.0001) when compared with the CYC group. This group also had less proteinuria levels (WMD=-0.55, 95%CI: -0.79 to -0.30, P﹤0.0001), lower degrees of SLE-DAI (OR=-1.80, 95%CI:-2.78 to -0.81, P=0.0004), and a lower adverse reaction rate. For example, gastrointestinal syndrome, irregular menstruation and leucopenia happened less frequently in the multitarget therapy group. However, hypertension was more prevalent in the multitarget therapy group. Conclusions: Multitarget therapy is an effective and safe intervention for inducing remission in lupus nephritis patients.